(untitled) (Annals of Medical Research, 2021)
Aim: In this study, we have investigated the oxidative effects of long-term electric field (EF) exposure on the skin and sciatic nerve tissue. It is seen that astaxanthin (AST) can have protective effects on the skin and sciatic nerve tissue with its powerful antioxidant effect. Materials and Methods: Rats are divided into 3 groups as control, EF, and EF + AST, with 10 animals in each group. 0.1 ml 0.9% sodium chloride for 30 days in the control group, 10 kV/m (50 Hz) EF 23 hours a day for 30 days in the EF group, 10 kV/m (50 Hz) EF 23 hours a day for 30 days and 100 mg/kg/day AST in 0.1 ml solution for 30 days in EF + AST group is given by gavage. Skin and sciatic nerve tissue are removed bilaterally and homogenized for biochemical analysis. Malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT) enzyme activities are studied in the skin and sciatic nerve. Results: The applied EF increases the MDA levels in the skin and sciatic nerve compared to the control group (p = 0.013, p = 0.011, respectively). While AST treatment decreased MDA levels in the skin and sciatic nerve compared to the EF group (respectively; p = 0.046, p = 0.039), SOD (respectively; p = 0.001, p = 0.009) and CAT (respectively; p = 0.004, p = 0.008) enzyme activities were increased.Conclusion: The results show that AST can be used to treat oxidative stress caused by the electric field due to its antioxidant properties.